Desain Game Edukasi Bertema Penerapan Akhlakul Karimah Menggunakan Framework Mechanics Dynamics Aesthetics - Selia Aysiah; Agus Komarudin; Rezki Yuniarti (Prosiding SISFOTEK, 2020)
Good character is a commendable attitude in accordance with Islamic teachings. Someone who has a moral character will always be liked by fellow human beings. A child does not understand whether what he is doing is dangerous or not, beneficial or detrimental, as well as right and wrong. The way to develop morality in children is by teaching them noble character. But in fact the environments that exist at this time more are considered as the cause of the occurrence of moral dedication, one of which is the rise of gadgets that contain game elements that are less educational. Based on these problems, it is necessary to present an educational game that is expected to be one of the ways to deliver the material so that children can participate in the learning of morality with good fun. In designing and compiling elements in a game one of them uses a framework method that has a sub method called Mechanics Dynamics Aesthetics (MDA). The MDA Framework was developed as a framework for understanding games through the perspective of users and developers. Based on the evaluation results of the game test through a questionnaire, where the aspects tested consist of the background of the respondent, the interaction of the respondent with the User Interface of the game, and the aesthetic or emotional challenge that must be felt when playing a good character game shows that the respondent feels happy and gets new knowledge about the character good and bad in the game.